A qualitative study on Shariah Committee in Islamic Banking Institution in Malaysia : the appointment process, academic qualification and expertise / Muhammad Faiz Azmi - Azmi, Muhammad Faiz (Academy of Contemporary Islamic Studies (ACIS), 2017)
The difference between Islamic banking and conventional banking is that Islamic banking transactions enforce Islamic transaction laws in banking practices. Thus, Islamic banks should have the capability to identify, understand and issue Islamic law in determining the status of the ongoing banking practice, Shariah compliant or not. In addition, Islamic banking should ensure every Islamic banking practices are compliance with Shariah on every operation on every time. This is important because the the foundation of Islamic banking establishment is the banking system compliance on Shariah law and it is a feature does not exist and contrary to conventional banking practices. To ensure compliance and the capability to understand Islam transaction laws, Islamic banking institutions have established Shariah committtee. Shariah committee is a body that has the largest authority in Islamic affairs. The main task of the Shariah committee is to advise and supervise the bank institution in Islamic affair. This committee consists of experts in various fields, especially in the field of usul fiqh (Islamic jurisprudence) and fiqh muamalat (Islamic financial). The expert on this committee expected to issue hukum properly and help ensure banks in Islamic banking principles secured. The purpose this study was to examine Shariah committee members who entrusted with ensuring Shariah compliance in banking institutions in Malaysia. This study attempts to obtain information about how the members of the committee appointed Shariah in Islamic banking institutions in Malaysia. In addition, this study will identify the relationship between the academic qualifications and the prospect to assume the position member of this committee. Hence, this study examines the expertise of the Shariah committee to determine the necessary expertise to carry out the duties and functions of the committee. The study also recommends a number of requirements who need to be prepare by individuals who want to assume the position as a member of the Shariah committee.